Taxonomy of Moenkhausia australis Eigenmann, 1908 (Characiformes, Characidae) with a discussion on its phylogenetic relationships - Reia, Lais; Vicensotto, Ana Maria P. F.; Oliveira, Claudio; Benine, Ricardo C. (Zootaxa, 2019)
The species Moenkhausia australis was described based on two specimens from arroyos Trementina and Chagalalina, Rio Paraguai basin, Paraguay. Its taxonomic history is complex and for many years the species was considered a synonym of Moenkhausia sanctaefilomenae. Moenkhausia australis shares a reticulated color pattern with the Moenkhausia oligolepis/M. sanctaefilomenae complex, being more similar within the species included in the complex to M. oligolepis, M. sanctaefilomenae, and M. forestii, with which it shares a prepelvic region laterally compressed, a feature also observed in Bario steindachneri. The laterally compressed prepelvic region is inferred to be putatively synapomorphic for the subgroup herein denominated as Moenkhausia oligolepis group. Our results, based on both molecular and morphological data, support the validity of Moenkhausia australis, which can be readily distinguished from the other members of the group by possessing the following combination of characters: complete lateral line, 23–27 scales in the lateral line, and five scales series above and below the lateral line. Our analysis also indicates three genetic structured populations of M. australis, from Rio Paraguai, upper Rio Paraná, and Rio Madeira basins. Since they are not diagnosable by morphological characters, we conservatively maintain these three genetic lineages as a single species.